Factors Influencing the Strategy for Increasing Regional Original Income in Buton Regency - Aci, Aci; Fatmawati, Fatmawati; Dewi, Andi Ratna Sari (PT. Riset Press International, 2023)
This research aims to analyze the factors that influence the strategy to increase Buton Regency's Original Regional Income (PAD). Regional income is an important source for district governments to finance development programs and public services. This research combines secondary data analysis with interviews with government officials, local economic experts, and other stakeholders to gain a deeper understanding of the external and internal factors that influence PAD. The findings show that national economic fluctuations, national tax policies, and local tax policies have a significant impact on Buton Regency's PAD. Apart from that, the potential of local natural resources and the active participation of local stakeholders are also key factors in the strategy to increase PAD. This research also highlights the importance of increasing internal capacity in regional financial management. In conclusion, this research provides a deeper understanding of the factors that influence PAD in Buton Regency and formulates recommendations for sustainable and adaptive PAD increase strategies.